2000
DOI: 10.1080/00288330.2000.9516943
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific burrow plasticity of an intertidal population ofCallianassa filholi(Crustacea: Decapoda: Thalassinidea) in relation to environmental conditions

Abstract: Burrow morphology and intraspecific burrow plasticity in relation to environmental conditions were examined for an intertidal population of Callianassa filholi Milne-Edwards, 1878 in southeastern New Zealand. Multivariate analysis of burrow features revealed no significant differences in burrow morphology between seasons. However, dissimilarities between burrows from different seasons could be identified and included differences in lateral extent, total length, and volume of burrows. These size parameters each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Pielou's evenness (Pielou, 1966) was calculated from OTU abundance matrices using the diverse test in Primer 6.1. Microbial community structure in shrimp burrows B Laverock et al shrimp behaviour, which would in turn impact on the biogeochemical and microbial signature of the burrow (Aller et al, 1983;Berkenbusch and Rowden, 2000;Bertics and Ziebis, 2009). Visually, the burrows of U. deltaura and C. subterranea are very different, and the two species show differing burrow-building and irrigation behaviours.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Pielou's evenness (Pielou, 1966) was calculated from OTU abundance matrices using the diverse test in Primer 6.1. Microbial community structure in shrimp burrows B Laverock et al shrimp behaviour, which would in turn impact on the biogeochemical and microbial signature of the burrow (Aller et al, 1983;Berkenbusch and Rowden, 2000;Bertics and Ziebis, 2009). Visually, the burrows of U. deltaura and C. subterranea are very different, and the two species show differing burrow-building and irrigation behaviours.…”
Section: Figurementioning
confidence: 99%
“…There is also likely to be some level of abiotic control. For instance, callianassid shrimp show intraspecific plasticity in burrow morphology according to prevailing environmental conditions, such as temperature and organic content (Berkenbusch and Rowden, 2000;Rowden and Jones, 1995). Marinelli et al (2002) found that the irrigation frequency of mimic burrows had no effect on the microbial community structure in sediment surrounding the burrow.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Some authors, such as Nickell and Atkinson (1995), believe that particular burrow features most likely relate to feeding strategies. Berkenbusch and Rowden (2000) suggested that the variation in burrow morphology of Biffarius (as Callianassa) filholi, in New Zealand waters is linked to seawater temperature and/or sediment organic content. Similarly, Griffis and Chavez (1988) suggested that sediment type and environmental factors such as tidal height and tidal exposure influenced the depth and burrow morphology of Neotrypaea (as Callianassa) californiensis and N. gigas in the Eastern Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dworschak et al (2012) burrow morphology varies in different families and genera, from the simple U-or Y-shaped structure for members of the Upogebiidae to complex burrow patterns with chambers and branches; such as those seen in the Callianassidae. Berkenbusch and Rowden (2000) suggested that some parameters such as seawater temperature and organic content of the sediment influence the burrow morphology of callianassid mud shrimps, while earlier, Griffis and Chavez (1988) suggested that burrow morphology was related to sediment type in two eastern Pacific species of callianassid. Biological factors, such as population density and competition with associated macroinfauna, have also been suggested to influence burrow morphology (Nash et al, 1984).…”
Section: Introductionmentioning
confidence: 99%